Role of dyslipidemia in the development of early-onset preeclampsia - Thabat J Al-Maiahy; Ali I Al-Gareeb; Hayder M Al-Kuraishy (Wolters Kluwer Medknow Publications, 2021)
Preeclampsia (PE) is a gestational-related disease presented with hypertension, peripheral edema, and proteinuria after 20 weeks of gestation. In PE, there are various metabolic changes like dyslipidemia. In addition, both PE and dyslipidemia are associated with changes of platelet indices. Thus, objective of the current study was to illustrate the potential role of dyslipidemia and platelet changes in pregnant women with PE. This case-control study involved 37 preeclamptic pregnant women as compared to 24 healthy pregnant women as controls. Blood pressure profile, lipid profile, proteinuria, and platelet indices were measured. Blood pressure profile was higher in preeclamptic pregnant women as compared to the controls (P < 0.01). There was a significant dyslipidemic status in preeclamptic pregnant women compared with the controls (P < 0.01). Platetetcrit (PCT) and platelet count (PC) were lower in preeclamptic pregnant women compared with the controls (P = 0.001). On the other hand, platelet distribution width (PDW), mean platelet volume (MPV), and platelet-large cell ratio (P-LCR) were higher in the pregnant women with PE as compared with the controls (P = 0.001). PCT and PC were insignificantly linked, while P-LCR, MPV and PDW were significantly correlated with total cholesterol, triglyceride, low-density lipoprotein (LDL)/high-density lipoprotein (HDL) ratio, systolic blood pressure, DBP, and MAP in preeclamptic patients compared with women of normal pregnancy. Both dyslipidemia and alterations in the platelet indices are correlated with blood pressure profile in PE. High MPV and PDW in association with high LDL/HDL ratio in pregnant women herald risk of PE.